PENGARUH PENAMBAHAN SERAT ROVING TERHADAP KAPASITAS LENTUR BALOK BETON BERTULANG - Apriyatno, Henry (Semarang State University, 2007)
Concrete is enervating the strength of pull and it is brittle in nature (it is tragile) that in aconstruction design the capacity of longitudinal concrete tension area is not computered. Theenervating concrete can be fixed by adding some fibres with the purpose to erect the concreteframe uniformly. Roving fibers are used at the composition of 1.9; 3.8; 5.7; and 7. 6% of theconcrete volume. The concrete mechanical change is determined by a concrete cylinder andconcrete block measuring 15cm x 20cm x 120cm put to experiment with their respective 15experimental objects. Refracted capacity experiment is gained from a chaste refracted block. Theresearch result shows that the fibre accretion to concrete causes the pressure capacity of concretecylinder to decrease significantly, whereas the strong pull of concrete increases. The concreteductility significantly increases, whereas the modular concrete elasticity significantly decreases, thecapacity of refracted block at the fibre compositions of 1.9 and 3.8% with the spread of 0.25h and0.5h gains a very good result.Keywords: roving fibre concreteÃÂ Beton memiliki kelemahan pada kuat tarik dan sifat getasnya rendah (mudah putus)sehingga dalam perencanaan kapasitas tampang beton daerah tarik tidak diperhitungkan.Kelemahan beton dapat diperbaiki dengan menambah serat yang memiliki tujuan menulangi betondengan serat secara uniform. Serat yang dipakai adalah serat roving pada komposisi 1,9; 3,8; 5,7;dan 7,6% dari volume beton. Perubahan mekanis beton diperoleh dari uji silinder beton dan balokbeton berukuran 15 cm x 20 cm x 120 cm masing-masing 15 benda uji. Pengujian kapasitas lenturdiperoleh dari balok lentur murni. Hasil penelitian menunjukkan dengan penambahan seratmenyebabkan kapasitas tekan silinder beton secara signifikan turun, sedangkan kuat tarik betonnaik. Sifat daktilitas beton meningkat secara signifikan sedangkan modulus elastisitas beton secarasignifikan turun, kapasitas lentur balok pada komposisi serat 1.9 % dan 3.8 % dengan penyebaran0.25 h dan 0.5 h diperoleh hasil yang paling baik.Kata Kunci: beton serat roving